Application of Additive Technology in Precision Casting - Halápi, Dávid; Varga, László (International Journal of Engineering and Management Sciences, 2020)
In this paper the surface of the prepared test specimens had been examined with light microscopy and surface roughness measurements. In order to improve the surface smoothness of PLA specimens, application of ethyl acetate was required. After this surface treatment, microscopic images were taken again. The melting and decomposition temperatures of the materials had been determined using derivatography. The chosen method was precision casting with gypsum molding. Also, the plaster molds had been burnt out according to the predefined melting and firing diagram. The measurement series shows that the samples produced by 3D printing can also be used in the field of precision casting. They provide greater freedom of design, more sophisticated pieces, and prototypes can be finished in a shorter amount of time.